Labor Analgesia Onset With Dural Puncture Epidural Versus Traditional Epidural Using a 26-G Whitacre Needle and 0.125% Bupivacaine Bolus: A Randomized Clinical Trial. Issue 3 (September 2018) - Wilson, S.H.; Wolf, B.J.; Bingham, K.; Scotland, Q.S.; Fox, J.M.; Woltz, E.M.; Hebbar, L.
Abstract : ( Anesth Analg . 2018;126:545–551) Lumbar epidural (LE) and combined spinal epidural are 2 techniques commonly used for labor analgesia. However, they are not without their disadvantages. An alternative may be the dural puncture epidural (DPE) technique, which allows medication to migrate into the intrathecal space via the epidural space. In the present study, the authors evaluated neuraxial labor analgesia onset following epidural bolus with a dilute local anesthetic solution (0.125% bupivacaine with 50 μg fentanyl) in active laboring parturients with and without DPE. The primary outcome of this study was the percentage of parturients in each group with adequate analgesia during active contraction 10 minutes after administering the epidural bolus.